Case Study Of Uninterrupted Rooftop Solar PV Implementation Strategy In Remote And Isolated Regions - Farid Wijaya; Muhamad Habibi (Institute of Advanced Knowledge and Science, 2026)
Equitable electricity access is still a challenge in the more isolated and remote parts of Indonesia, where electricity access is geographically limited, operationally expensive and heavily dependent on highly emitting diesel power plants. In this study, a occupational health and safety-compliant implementation strategy of household rooftop PV systems is analyzed to enable energy transition and decarbonization using tiered load scenarios based on household size and efficient appliance profiles. The results show a daily energy demand ranging from 2.66–5.71 kWh/day and a required PV capacity between 0.79 and 1.69 kWp. From an economic perspective, rooftop PV LCOE without battery storage is estimated at Rp 1,475–1,485/kWh, while the hybrid PV-BESS configuration ranges from Rp 2,753 to 2,772/kWh. The battery option, while more expensive, is still relevant for regions with high nighttime demand, unreliable supply or for off-grid operation. In Scenario 5 with , rooftop PV becomes increasingly competitive at community scale, with LCOE declining to approximately Rp 2,217/kWh (for 50 households), well below diesel-based power supply costs of about Rp 4,791/kWh. Second, community-scale PV can avoid more than 81.6 ton CO₂e per annum by replacing diesel generation. The implementation of PV rooftop in remote and isolated regions must comply with the occupational health and safety aspect as a core requirement, especially for DC protection, grounding, quality of connector, roof structural integrity, and operation certification.